Study of Electronic and Dielectric Properties of L-Arginine Semimalonate - Sreepad, H. R. (Asian Journal of Science and Applied Technology, 2021)
First-principles calculations have been done on the L-arginine semimalonate C₉H₁₈N₄O₆ crystal based on Density Functional Theory. The Triclinic structure of Nitrilotrisethylene carbamic acid has been simulated using this formalism and the structural parameters have been found out. The Electron Density of States (EDOS) has been computed in the material using the Electronic structure calculation code of the software Quantum-Espresso which gives a Band gap of 2.35 eV. This value is found to be close to the value exhibited by semiconducting materials and photonic band gap materials. The value of polarizability has also been calculated. Its value comes out to be 77.40 Å3, 77.08 Å3, 76.55 Å3 along x,y and z axis with average value of 77.01 Å3. The values of Phonon modes have been computed using the ph.x program code of quantum espresso software. The values of computed phonon modes range from 0 cm−1 to 8012 cm−1.